Analisis Pukulan Gyaku Tsuki Pada Siswa Remaja Karate Dojo Kabupaten Karanganyar Tahun 2024 - Galih Putri Miranti; Teguh Andibowo; Slamet Sudarsono; Rendra Agung Prabowo; Wisnu Mahardika; Erik Teguh Prakoso6 (Journal on Education, 2024)
The purpose of this study was to determine the ability of Gyaku tsuki Punches in Karanganyar Regency Karate Dojo Youth Students in 2024. This research method is quantitative descriptive research with the characteristics of the absence of hypotheses and the data obtained will be presented. The method used is a survey, with a research instrument in the form of a skill test of the basic technique of gyaku tsuki punches performed 2x attacking which aims to determine the Analysis of Gyaku Tsuki Punches on Teenage Karate Dojo Students Karanganyar Regency Year 2023. The sample of this study were karate students with the age category 12-17 years totaling 20 people. Based on the results of data analysis, that those who have punch skills in the good category with a score of 12 - 16 are 4 students or 20% of the total sample, then those who have punch skills in the sufficient category with a score of 8 - 4 are 13 students or 65% of the total sample, and those who have punch skills in the deficient category with a score of 4 - 7 are 3 students or 15% of the total sample studied. Based on the results of research and discussion, it is concluded that: students who are classified as "good" are 4 students (20%), "enough" are 13 students (65%), and "less" are 3 students (15%). The results of the study concluded that the gyaku tsuki punch skills of adolescent karate dojo students in Karanganyar Regency in 2024 were in the sufficient category.